1996
DOI: 10.1007/bf02525448
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time X‐ray powder diffraction investigations on cocoa butter. I. temperature‐dependent crystallization behavior

Abstract: The crystallization behavior of cocoa butter has been investigated by means of real‐time X‐ray powder diffraction. Two procedures have been followed: cooling from 60°C at a constant rate until maximum solidification has taken place; and cooling from 60°C in 2 min to a constant solidification temperature. It appears that all polymorphic forms of cocoa butter, with the exception of the β form, can be formed from liquid. The solidification temperature appears to be the most important crystallization parameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(71 citation statements)
references
References 11 publications
7
61
3
Order By: Relevance
“…TAG mixtures also show differences in phase stability. For example, milk fat is β′-stable (6) while cocoa butter has β as the most stable phase (7,8).…”
mentioning
confidence: 99%
“…TAG mixtures also show differences in phase stability. For example, milk fat is β′-stable (6) while cocoa butter has β as the most stable phase (7,8).…”
mentioning
confidence: 99%
“…Our CB samples also shows XRD patterns which look much like that of β-VI (Figure 1), while its melting point (31.43℃) was closer to β-V (30.8~33.8℃), as reported by Chapman et al (1971) and Wille and Lutton (2001). Malssen et al (1996) also observed that in some CB samples originated from twelve different countries, XRD patterns of β-phase are closer to those of β-VI but their m.p. resembled that of β-V.…”
Section: Resultsmentioning
confidence: 73%
“…Polymorphism is defined as the ability of a substance to exist in more than one crystalline form in a crystal lattice (Oh and Swanson, 2006). This polymorphism, is a critical step in chocolate making, and has been studied extensively in the last century (Wille and Lutton, 1966;Chapman et al, 1971;Malssen et al, 1996;Schenk and Peschar, 2004). Several techniques such as differential scanning colorimetery, light microscopy, pulsed nuclear magnetic resonance, and X-ray diffractometer (XRD) have been used to determine polymorphic structures of lipids (Guthrie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Real time XRD studies using laboratory X-ray diffractometers have been carried out to observe the evolving crystalline structure in cocoa butter in both static (Van Malssen et al, 1996, 1996a and sheared crystallisation (Sonwai, 2002). Synchrotron XRD offers improved resolution, rapid data collection and simultaneous small (SAXS) and wide (WAXS) angle measurements, corresponding to the long and short range spacing in the crystal lattice .…”
Section: Introductionmentioning
confidence: 99%